GE_GERICHTE P/9338/2014 vom 23. Mai 2018 - GE Cour de justice (2018)
CLASSEMENT DE LA PROCÉDURE ; FRAIS JUDICIAIRES ; PRÉVENU ; FAUTE ; PRÉSOMPTION D'INNOCENCE ; DÉPENS ; INDEMNITÉ(EN GÉNÉRAL) | CPP.426.al2; CPP.429; CPP.433.al1